The Influence of the Snowball Throwing Learning Model on Pythagorean Theorem Material on Learning Outcomes - Sefira, Rani; Setiawan, Agus; Hidayatullah, Rizky; Choirudin; Darmayanti, Rani (CV. Edutechnium Indonesia, 2024)
Lack of understanding by students during teaching and learning activities is a problem experienced in learning. One of the causes is that the learning process is less effective in delivering learning, so student learning outcomes tend to be low. This study aimed to determine the effect of the snowball throwing learning model on Pythagorean theorem material on the mathematics learning outcomes of class VIII students at MTs Darul A'mal. The samples used in this research were classes VIII C and VIII D, each numbering 30 students. This type of research is a quasi-experimental quantitative research method (Quasi-Experimental Design) with one class as the experimental class and one as the control class. Data collection techniques include interviews, documentation and tests (pre-test and post-test). Tests were conducted to determine student learning outcomes before and after using the snowball-throwing learning model. This study concluded that the snowball-throwing learning model affected student learning outcomes for class VIII MTs Darul A'mal Darul A'mal Metro. This is evident from the results of data analysis from the t-test formula with a value of t-count = 2.072 > t-table = 2.069, then Ho is rejected, and Ha is accepted.